Lizy

\(\left\{{}\begin{matrix}\left(x-1\right)^2-\left(y+1\right)^2=0\\x+3y-5=0\end{matrix}\right.\)

\(\left\{{}\begin{matrix}\left(x-1\right)^2-\left(y+1\right)^2=0\\x+3y-5=0\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}\left(x-1-y-1\right)\left(x-1+y+1\right)=0\\x+3y-5=0\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}\left(x-y-2\right)\left(x+y\right)=0\\x+3y-5=0\end{matrix}\right.\)

=>\(\left[{}\begin{matrix}\left\{{}\begin{matrix}x-y-2=0\\x+3y-5=0\end{matrix}\right.\\\left\{{}\begin{matrix}x+y=0\\x+3y-5=0\end{matrix}\right.\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}\left\{{}\begin{matrix}x-y=2\\x+3y=5\end{matrix}\right.\\\left\{{}\begin{matrix}x+y=0\\x+3y=5\end{matrix}\right.\end{matrix}\right.\)

=>\(\left[{}\begin{matrix}\left\{{}\begin{matrix}-4y=-3\\x-y=2\end{matrix}\right.\\\left\{{}\begin{matrix}-2y=-5\\x+y=0\end{matrix}\right.\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}\left\{{}\begin{matrix}y=\dfrac{3}{4}\\x=y+2=\dfrac{3}{4}+2=\dfrac{11}{4}\end{matrix}\right.\\\left\{{}\begin{matrix}y=\dfrac{5}{2}\\x=-\dfrac{5}{2}\end{matrix}\right.\end{matrix}\right.\)


Các câu hỏi tương tự
Tran Phut
Xem chi tiết
ILoveMath
Xem chi tiết
DUTREND123456789
Xem chi tiết
DUTREND123456789
Xem chi tiết
Lizy
Xem chi tiết
ILoveMath
Xem chi tiết
kietdvjjj
Xem chi tiết
minh ngọc
Xem chi tiết
ILoveMath
Xem chi tiết